PENERAPAN MODEL PEMBELAJARAN SSCS (SEARCH, SOLVE, CREATE AND SHARE) TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Rini Apriyanti; Uba Umbara; Evan Farhan Wahyu Puadi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2017)
Rini Apriyanti (NIM : 133223006), Using of SSCS (Search, Solve, Create and Share) Learning Model to Enhancement Mathematical Problem Solving Ability of Middle School Students. This research is based on the effort to improve students mathematical problem solving ability which get the learning model of SSCS (Search, Solve, Create and Share). Through the experimental method obtainded the initial test results of the control class with an average value of 7,20 and the average value of the experimental class 7,64. white in the final test obtained the average value of control class 9,14 and experimental class 13,10. From the results of initial data analysis and final sample data, it can be concluded that mathematics learning using SSCS (Search, Solve, Create and Share) learning model is better than mathematical problem solving ability of students who get conventional learning model. As for enhancement of mathematical problem solving ability of students experimental class is in the medium category. Other then that, from result the questionnaire of student responses known that student show positive response to SSCS learning model.